COVID-19's impact on athletes: reduced cardiorespiratory fitness after a SARS-CoV-2 infection - Hasler, E.; Widmann, M.; Haller, B.; Gaidai, R.; Venhorst, A.; Meyer, T.; Reinsberger, C.; Niess, A. M.; Röecker, K.; COSMO-S Research Group. (Medicine & Science in Sports & Exercise, 2025)
Objective This study aimed to identify potential changes in cardiorespiratory fitness among athletes who had previously been infected with severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2).